(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In order to successfully master the language in natural conditions, certain abilities are necessary. Note that the very term linguistic (linguistic) abilities is conditional. In this case, we do not mean the actual ability to master any of the national languages in otnogenesis, but a predisposition to learning languages. Susceptibility to languages does not exist separately, in isolation from other abilities. [7]. T.M. Rumyantseva defines language ability “as a mental and psychophysiological function of a person, biologically and genetically incorporated, but formed and developed socially on the basis of the anatomical and physiological and neurophysiological organization of a person; a function that provides the ability of the human psyche to reflect and generalize external language material, translating it into special internal codes in the form of unconscious and conscious rules of the language" [6, 170]. The key in this definition, in our opinion, is the recognition of the combination of biological and social; this combination provides the possibility of generalizing and "translating" the result of processing the input into a set of rules both with the participation of consciousness and unconsciously.